Design of accelerating cavities for UNDULAC - Polozov, S.M.; Safikanov, P.R.; Tatsyuk, O.A. (Вопросы атомной науки и техники, 2012)
The acceleration of high intensity low beta ion beams is one of the priority tasks of applied accelerating technology. The space charge effect is a key problem appeared for high intensity ion beam acceleration. The influence of space charge can be decreased by the ribbon beam acceleration. The linear undulator accelerator (UNDULAC) was proposed by E.S. Masunov for this aim. In this paper the accelerating cavity for UNDULAC will considered, H-type and E-type cavities will studied, the electrodynamics parameters will defined and optimization of fields distribution will done. The especially designed method of drift tubes geometrical parameters synthesis will discussed and tested.